Tamm Review: Postfire landscape management in frequent-fire conifer forests of the southwestern United States - Stevens, Jens T.; Haffey, Collin M.; Coop, Jonathan D.; Fornwalt, Paula J.; Yocom, Larissa; Allen, Craig D.; Bradley, Anne; Burney, Owen T.; Carril, Dennis; Chambers, Marin E.; Chapman, Teresa B.; Haire, Sandra L.; et al. (Forest ecology and management, 2021)
•Recently-burned area in southwestern US forests is increasing.•Landscape context, values, and future trajectories of change can inform management.•Postfire forest patches can be managed for resilience to future fires.•Novel reforestation practices may help adapt to future climate and fire in some areas. The increasing incidence of wildfires across the southwestern United States (US) is altering the contemporary forest management template within historically frequent-fire conifer forests. An increasing fraction of southwestern conifer forests have recently burned, and many of these burned landscapes contain complex mosaics of surviving forest and severely burned patches without surviving conifer trees. These heterogeneous burned landscapes present unique social and ecological challenges. Severely burned patches can present numerous barriers to successful conifer regeneration, and often contain heavy downed fuels which have cascading effects on future fire behavior and conifer regeneration. Conversely, surviving forest patches are increasingly recognized for their value in postfire reforestation but often are overlooked from a management perspective. Here we present a decision-making framework for landscape-scale management of complex postfire landscapes that allows for adaptation to a warming climate and future fire. We focus specifically on historically frequent-fire forests of the southwestern US but make connections to other forest types and other regions. Our framework depends on a spatially-explicit assessment of the mosaic of conifer forest and severely burned patches in the postfire landscape, evaluates likely vegetation trajectories, and identifies critical decision points to direct vegetation change via manipulations of fuels and live vegetation. This framework includes detailed considerations for postfire fuels management (e.g., edge hardening within live forest patches and repeat burning) and for reforestation (e.g., balancing tradeoffs between intensive and extensive planting strategies, establishing patches of seed trees, spatial planning to optimize reforestation success, and improving nursery capacity). In a future of increasing fire activity in forests where repeated low- to moderate-severity fire is essential to ecosystem resilience, the decision-making framework developed here can easily be integrated with existing postfire management strategies to optimize allocation of limited resources and more actively manage burned landscapes.